(untitled) (Medical Forum Monthly, 2022)
Objective: The purpose of this study was to examine if early involvement in cardiac rehabilitation (CR) decreases readmissions after heart failure (HF) hospitalization. Study Design: A Retrospective Study Place and Duration of Study: This study was conducted at the University Hospital Center "Mother Teresa" in Tirana, University Hospital "SHEFQET NDROQI", AMERICAN Hospital, HYGEA Hospital, and "Our Lady of Good Counsel, Tirana" from January 2019 - November 2021. Materials and Methods: There were 120 patients of both gender had heart failure included in this study. Age of the patients was between 18-80 years of age. Patients were equally divided in two groups. Group I had 60 patients were discharged after getting 30-days hospitalization without getting cardiac rehabilitation while in group II 30-patients received at-least 1-sesssion of cardiac rehabilitation in hospitalization. Outcomes among both groups were compared in terms of readmission because of HF. SPSS 24.0 was used to analyze all data. Results: Among 120 patients, 69 (57.5%) were males and 61 (42.5%) were females. Mean age of the patients was 53.24±11.64 years and had mean BMI 24.11±6.37 kg/m2. There were 71 (59.2%) patients had hypertension and diabetes mellitus was found in 44 (36.7%) cases, Smoking history was found in 57 (47.5%) cases. There were 10 (8.3%) cases had heat stroke among all cases. Early cardiac rehabilitation dramatically decreased hospital readmissions and cardiac mortality in patients. The cardiac rehabilitation group that had re-hospitalization had higher rates of diabetes, hyperkalemia, and low PETCO2. An independent risk factor for re-hospitalization was low PETCO2 (Partial pressure of end-tidal carbon) at anaerobic threshold ( ≤33.5 mmHg). Conclusion: We found that people with acute myocardial infarction who started cardiac rehabilitation right away had fewer major cardiac events later on. As a risk factor for readmission, decreased PETCO2 at the anaerobic threshold can be utilized to evaluate the efficacy of early cardiac rehabilitation.